Effects of recombinant human growth hormone on proliferation and differentiation of cementoblast and ERK1 / 2, JNK / SAPK and p38MAPK signaling pathway: Effects of rhGH on p38MAPK signaling pathway - Wu, Liuzhong; Shen, Danyang; Guo, Chuanbo (Cellular and Molecular Biology, 2022)
To investigate the effects of recombinant human growth hormone on the proliferation and differentiation of cementoblast and the signal pathways of ERK1 / 2, JNK / SAPK and p38MAPK, osteoblasts (OCCM-30) were cultured in vitro. The OCCM-30 was treated with different concentrations of recombinant human growth hormone (rhGH) (0, 10, 50 ng/mL) for 1 d and 2 d, respectively. MTT assay was used to test the proliferation of OCCM-30 cells by rhGH. The effect of BSP, OPN, OCN and ALP genes was detected by RT-PCR after one day. The activity of alkaline phosphatase (ALP) was detected after treatment with OCCM-30 for five days at different concentrations of rhGH. After treatment with OCCM-30 at 100 ng/mL rhGH for 0 min, 5 min, 10 min, 15 min, 30 min and 60 min, the phosphorylation levels of ERK1/2, JNK/SAPK and p38MAPK were detected by Western blot. Results showed that rhGH could promote the proliferation of OCCM-30 cells, and the proliferation of OCCM-30 cells increases with the increase of rhGH concentration. After one day of culture, the levels of the BSP and ALP genes increased with the increase of rhGH concentration (P<0.05); the OPN gene level in the 10 ng/mL group was significantly higher than that in the blank group, and the 50 ng/mL group was significantly lower than the blank group. (P<0.05); OCN gene levels in the 10 ng/mL group and 50 ng/mL group were not significantly different from those in the blank group (P>0.05). Compared with the blank group, the ERK 1/2 phosphorylation level increased at 5 min in the 100 ng/mL group, reached the maximum at 10 min, decreased significantly at 15 min, decreased to the original level at 30 min, and had no significant change in ERK 1/2 total protein level; 100 ng/mL rhGH had no significant effect on SAPK/JNK, p38MAPK phosphorylation and total protein levels in OCCM-30 cells (P>0.05). It was concluded that 10ng/mL and 50ng/mL rhGH could promote the proliferation of OCCM-30 cells and promote the expression of the BSP gene and ALP gene. Low-dose rhGH is beneficial to OPN gene expression, and high-dose rhGH inhibits OPN gene expression. 100 ng/mL rhGH promoted the ERK 1/2 pathway and had no effect on the SAPK/JNK and p38 MAPK pathways.